Performance Evaluation of Pakistan’s Mutual Fund through CAPM and Fama French 3-Factor Model - Fatima, Syeda Zain; Haroon, Muhammad (Archives of Business Research, 2018)
Mutual fund is selection for the common investors for investing in to the capital market. In the research paper Capital Asset Pricing Model (CAPM) and FAMA French 3 factor model applied for the measurement and evaluate the performance of the mutual fund. Daily data of mutual fund which are selected in open ended mutual fund of Pakistan and daily data collected from 2010 to 2016. Then applied these models and Capital Assets Pricing Model showed the significant result and R² value more co-related with the market returns and premium. FAMA French 3 factor model showed the not good results with the two factors SMB and HML. Time series regression model are applied between two competing models.